Adsorption of Direct Blue 2 Dye by Dry Biomass of Bacillus cereus from Aqueous Solution - Khazaal, Duaa Sameer; Hatif, Zainab Hani; Mahdi, Zinah Mohammed; Hussain, Sajida Frhan (Iraqi Journal of Science, 2023)
One of the significant environmental problems is the pollution of water by dyes;. Biological treatment method was used, which is one of the effective ways to reduce this sort of pollution as it is environment friendly, economic and does not require any expertise. Under controlled conditions, this study estimated the efficacy of dry biomass for Bacillus cereus to reduce Direct Blue 2 dye from the aqueous solution. The optimum conditions such as pH values, contact time and concentration of dyes, were used in this research. The end results showed that the adsorption efficiency, when using a weight of bacterial biomass 0.2 g/50mL, reached 69.2% at a concentration of 10 ppm after one hour at 40°C and pH5. While it reached 54.6% for a concentration of 15 ppm with a contact time of three hours and pH 7. At 40oC and one hour contact time, the adsorption efficiency for a concentration 20 ppm was 46.5% at pH9. The optimum conditions for the highest adsorption efficiency were achieved after one hour and pH5.